Plan de Gestión de Recursos Humanos, Comunicaciones y Adquisiciones para Condominios Marisol según la Guía del PMI - Rodríguez-Porras, Noelia (Instituto Tecnológico de Costa Rica, 2014)
The right management of the projects is the success key of a company, the literature divided this administration on nine big areas each one of them on the different company issues. The work will take part on the human resources, communication and acquisitions areas. To achieve the development of this subject were raised the follow objectives: Analyze the current administration system, select the process and helpful tools for the control of the chosen areas, develop new process and tools on the current company project management and elaborate the management process manual the company needs. For the analysis mentioned before was used the Project Management Institute (PMI) on the Pmbok, to know the company’s current state, what comes to the management was observed and investigated some members involved on the constructive works management, the same way was evaluated the used tools on the studied areas. The wrong management brings troubles such as poor quality work or delay on the delivery dates and increased costs caused by the productivity decrease and control loss over the different tasks. For this reasons is presented the guide to take as foundation the operations relate with human resources with communication and acquisitions the project needs.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2014.
Keywords: Administración; Gestión; Adquisiciones; Productividad